LOCAL GOVERNMENT IN UZBEKISTAN: LEGAL AND ORGANIZATIONAL MECHANISMS OF INTERACTION BETWEEN COUNCIL AND AUTHORITY - Сайфиддинов, Аклиддин (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2025)
The article presents a legal and institutional analysis of the interaction between local councils of people's deputies and executive authorities (hokimiyats) in the Republic of Uzbekistan. It examines the main legal acts defining the modern system of local public administration and the division of powers between representative and executive branches of authority. The study is based on the principles of decentralization, popular sovereignty, and accountability, and includes a comparative legal analysis of foreign models (France, Poland, Turkey), as well as theoretical approaches by E. Ostrom, J. Pierre, B. Peters, R. Dahl, and other scholars. It is shown that the existing system requires improvement of coordination procedures, the introduction of transparent reporting mechanisms for hokims before councils, and the expansion of civil society participation. The conclusion substantiates the necessity of transitioning to a stable institutional partnership model based on the principles of legality, transparency, and governance efficiency.